Translation studies in the Philippines navigating a multilingual archipelago - Moratto, Riccardo 1985-; Bacolod, Mary Ann G. (Routledge advances in translation and interpreting studies, 2024)
"The contributors to this book examine the state, development, issues, practices and approaches to translation studies in the Philippines. The Philippines is a highly multilingual country, with many indigenous languages and regional dialects spoken alongside foreign imports, particularly English and Spanish. Professor Moratto, Professor Bacolod, and their contributors analyse the different roles that translation plays across an extensive range of areas, including disaster mitigation, crisis communication, gender bias, marginalization of Philippine languages, empowering communities, national consciousness, and views on sex, gender, and sexuality. They look at a range of different types of translation, from the translation of biblical texts to audio-visual translation, and machine translation. Emphasising the importance of translation as an interdisciplinary field, they use a variety of analytic lenses, including anthropological linguistics, forensic linguistics and performance arts, among others. A comprehensive resource for scholars and practitioners of translation, as well as a valuable reference for scholar across a wider range of humanities and social science disciplines in examining the culture and society of the Philippines"--Provided by publisher.